2013
DOI: 10.12932/ap0362.32.3.2014
|View full text |Cite
|
Sign up to set email alerts
|

Is fractional exhaled nitric oxide (FeNO) associated with asthma control in children?

Abstract: FeNO levels were increased in ICS-treated asthmatic patients with less asthma control, albeit with no statistically significance. However, FeNO levels correlated with poor asthma control status in ICS untreated cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 27 publications
1
14
1
Order By: Relevance
“…Some studies have reported significant differences in exhaled NO levels between controlled and uncontrolled asthmatic children and showed that children with levels below 20 ppb had significantly higher scores in Asthma Control Test (ACT) and child‐ACT (C‐ACT) . Additionally, exhaled NO levels correlated with poor asthma control status in inhaled corticosteroids (ICS) untreated cases . Exhaled NO also proved to be a useful tool that distinguishes asthma severity and asthma control in children when FEV 1 fails to do it as well as when its defined by a clinical evaluation .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported significant differences in exhaled NO levels between controlled and uncontrolled asthmatic children and showed that children with levels below 20 ppb had significantly higher scores in Asthma Control Test (ACT) and child‐ACT (C‐ACT) . Additionally, exhaled NO levels correlated with poor asthma control status in inhaled corticosteroids (ICS) untreated cases . Exhaled NO also proved to be a useful tool that distinguishes asthma severity and asthma control in children when FEV 1 fails to do it as well as when its defined by a clinical evaluation .…”
Section: Discussionmentioning
confidence: 99%
“…FeNO levels also differed significantly between the controlled and uncontrolled subgroups (8.5 ppb vs. 26.4 ppb, p-0.03). 91 Another cross sectional study recruited children with stable asthma (majority were on ICS, majority were allergic defined by a radio-allergosorbent test class 2 or higher or a positive skin test). 92 Children with insufficient, acceptable, or good control of asthma had FeNO levels of 28 ppb, 15 ppb, 11ppb; respectively (p<0.01).…”
Section: Children (Ages 5 To 18)mentioning
confidence: 99%
“…A study conducted in Thailand showed that FeNO levels increased in inhaled corticosteroid (ICS)‐treated asthmatic patients with poor asthma control . Information regarding FeNO levels in the prediction of asthma exacerbation (AE) in children is insufficient.…”
Section: Introductionmentioning
confidence: 99%